ANALISIS STRATEGI POSITIONING UNIVERSITAS HANG TUAH ( Blue Ocean Campus ) - Herman (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
This research aimed to analyze the positioning strategy of Hang Tuah University Surabaya in the minds of customers, by analyzing the slogan "Blue Ocean Campus". This research used a quantitative and qualitative approach, data used are primary and secondary data, primary data by distributing questionnaires and interviews, while secondary data was taken from the website of the University studied. Research shows Hang tuah University positioning based on the importance criteria the majority of respondents expressed less valuable, results also show a comparison Slogan Hang Tuah University with other universities. Attributes are used as the basis of positioning Hang Tuah university "Blue Ocean Campus" has not been considered important by informants when compared with the attributes that are used by other universities.